Analysis of Pesticide Residues of Chlorpyrifos and Mancozeb in Green Beans (Phaseolus vulgaris) in Traditional and Modern Markets in Surabaya City: Analisa Residu Pestisida Klorpirifos dan Mankozeb pada Buncis (Phaseolus vulgaris) di Pasar Tradisional dan Modern Kota Surabaya - Sergio Helios; Dwi Haryanta; Achmadi Susilo (Agrotechnology Study Program, Faculty of Agriculture, Wijaya Kusuma Surabaya University, 2026)
This study aimed to analyze and compare the levels of pesticide residues of chlorpyrifos and mancozeb in green beans (Phaseolus vulgaris) marketed in traditional and modern markets in Surabaya City. The research employed a quantitative survey method with a comparative approach. Green bean samples were collected from several traditional and modern markets and analyzed in the laboratory using Gas Chromatography–Mass Spectrometry (GC-MS). The results showed that chlorpyrifos and mancozeb residues were detected in all samples from both market types. However, the measured residue levels were still below the established Maximum Residue Limits (MRLs). Generally, pesticide residue levels in green beans from traditional markets tend to be higher than those from modern markets. These differences were presumably related to variations in distribution systems, postharvest handling, and quality standards applied in each market. The findings indicate that green beans marketed in Surabaya generally meet food safety standards, although continuous monitoring of pesticide residues in fresh vegetables remains necessary